Relationship between Academic Self-Efficacy and Student Procrastination of BK FIP UNP in Completing the PLKP-S Report - Dira Yulmi; Neviyarni Neviyarni (Universitas Negeri Padang, 2020)
Procrastination is a form of activity that shows individuals delaying all types of activities, although sometimes the form of delay will have a negative impact on the individual. Procrastination is influenced by several factors, one of which is self-efficacy. This study aims to describe (1) academic self-efficacy (2) procrastination, and (3) to examine the relationship between academic self-efficacy and procrastination of BK FIP UNP students in completing the PLKP-S report. This research is a descriptive and correlational research. The study population was the students of BK FIP UNP who had implemented PLKP-S with a total of 149 students. The number of samples was 109 students obtained by simple random sampling technique. The results showed that (1) In general, the academic self-efficacy of BK FIP UNP students in completing the PLKP-S report was in the moderate category, (2) In general the procrastination of BK FIP UNP students in completing the PLKP-S report was in the medium category, and (3) There is a significant negative relationship between academic self-efficacy and the procrastination of BK FIP UNP students in completing the PLKP-S report.